Peripartum cardiomyopathy: current state of the problem - Ya.M. Lutai (Медицина неотложных состояний)
Peripartum cardiomyopathy (PCMP) is cardiomyo-pathy with left ventricular systolic dysfunction that develops in late pregnancy or in the first months of postpartum period. Clinical manifestations can vary from mild or moderate to severe symptoms of heart failure with significant functional limitation and high mortality. PCMP has a rather heterogeneous and incompletely studied pathophysiology, which includes hormonal, vascular, metabolic, and immunological pathways, whose implementation becomes possible on the background of genetic predisposition. Treatment is based on heart failure therapy, taking into account the risks associated with pregnancy and lactation. Bromocriptine is being considered as a specific therapy; however, the level of evidence for such treatment is insufficient. The article covers basic information about the pathophysiology, diagnosis, prognosis, prevention and treatment of PCMP at the current stage. For writing this review, the literature search was conducted using the MEDLINE, Scopus, and Web of Science databases.